Answer: x= -6 x=6
Step-by-step explanation:
expand the equation so you get (x-6)(x+6) and then set the equal to zero and solve
Answer:
A. 4
Step-by-step explanation:
Constant of proportionality (k) = y/x
We can use the coordinates of any point on the line to find k.
Let's use (2, 8)
Constant of proportionality (k) = 8/2
Constant of proportionality (k) = 4
Answer:
<em>Factored Form: </em><em> </em><em>( y - 2 )( 3y + 7 )</em>
Step-by-step explanation:
<em>1. Let us first write down the problem at hand: </em>3y^2 + y - 14
<em>2. Now let us break this expression into groups: </em>
3y^2 - 6y + 7y - 14 ⇒ ( 3y^2 - 6y )( 7y - 14 )
<em>3. Factor 3y from 3y^2 - 6y:</em>
3y^2 - 6y ⇒ 3y( y - 2 )
<em>4. Factor 7 from 7y - 14:</em>
7y - 14 ⇒ 7( y - 2 )
<em>5. Substitute Step #3, 4 ⇒ Step #2:</em>
3y( y - 2 ) + 7( y - 2 )
<em>6. Factor common term y - 2:</em>
<em>Answer: ( y - 2 )( 3y + 7 )</em>